Knowledge Management and Storytelling as Social Transformation Tools in Educational Tourism on the Citarum River - Delamontano, Eldo; Endyana, Cipta; Winoto, Yunus; Novianti, Evi (Jurnal Masyarakat Madani Indonesia, 2025)
Developing sustainable tourism necessitates innovative approaches that integrate environmental conservation, community engagement, and effective knowledge transfer. This study investigates the power of storytelling and knowledge management as catalysts for social transformation within educational tourism along Indonesia's highly polluted Citarum River. Using a mixed-methods approach, the research collected quantitative data from 79 university students via questionnaires assessing their knowledge and perceptions of the Citarum River and sustainable tourism. Qualitative data came from a content analysis of "Menjaga Citarum" (Preserving Citarum) educational materials, which wove together historical narratives, ecological facts, and local cultural values. The findings reveal that storytelling, when combined with direct environmental action and participatory learning, significantly boosts students' environmental awareness and emotional engagement. Participants showed a greater understanding of pollution issues and a stronger commitment to sustainable behavior, highlighting the importance of community-based knowledge systems. This study demonstrates how local narratives and experiential learning can foster ecological responsibility and social engagement, offering practical guidance for impactful educational tourism programs.